(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2022)
Family persecution is a global phenomenon known to all human societies in varying degrees and in different forms, and the difference between societies in this regard is in terms of the size and severity of persecution on the one hand and its causes on the other hand, as well as the conditions and historical stages that societies go through, and this means that this phenomenon It is not a phenomenon that is closely related to a particular society and not to others, despite the difference in its severity and causes.